Efektivitas Media ROPITA (Round Spin Table) Terhadap Peningkatan Pengetahuan Kesehatan Gigi Siswa Sekolah Dasar - Dwi septiarini; Yulyana Sendia Martina; Hayatunnufus; Rohisotul Laily (Jurusan Keperawatan Gigi Poltekkes Kemenkes Makassar, 2025)
Oral health problems in children are still a significant problem in Indonesia. Based on Basic Health Research (Riskesdas) data in 2018, it shows that the percentage of cavities is 88.8% while only 2.8% of children apply the right way to brush their teeth. The 2023 Indonesian Health Survey (IHS) also showed a dental caries rate of 43.6% in Semarang City. One of the efforts made to reduce caries rates through a promotive and preventive approach by utilizing media as a means of increasing dental health knowledge is ROPITA (Round Spin Table) media. This study aims to determine the effectiveness of ROPITA (Round Spin Table) media on increasing dental health knowledge of elementary school students. The research method used is true experimental design which includes pre-test and post-test with control group design. This study involved two different groups of subjects, namely the intervention group and the control group which were randomly selected. The results of this study showed that the p-value was 0.000 (p < 0.05), meaning that there was an effectiveness of ROPITA (Round Spin Table) media on increasing the knowledge of elementary school students and the Cohen's D value of 0.86, which showed a large effect of the intervention group. Keywords : Media; ROPITA (Round Spin Table); elementary school students; knowledge